(untitled) (AMJ (Advanced Medical Journal), 2023)
Background and Objectives: Coagulase-negative staphylococci are commensal bacteria inhabiting human. Isolation of these bacteria from healthcare-associated and community infections is increasingly observed with resistance response to many antibiotics. The study aimed to identify the clinical and antimicrobial resistance pattern of coagulase-negative staphylococci isolated from various healthcare-associated and community-acquired infections. Methods: This cross-sectional study was conducted in Shar Teaching Hospital and San Clinical Laboratory for a period of one year starting from 1st of November 2019.Isolated coagulase-negative staphylococci were collected from various hospitals and clinical laboratories. The isolate species were confirmed by several tests including VITEK® 2. VITEK® 2 systems was also used to determine the susceptibility to different antibiotics including cefoxitin, oxacillin gentamicin, linezolid, and glycopeptide agents’ teicoplanin and vancomycin which were tested also by E-test. Results: Coagulase-negative staphylococci were isolated from urine specimens (23%), followed by blood samples (20%), sterile body fluids (12%), and others. From one hundred isolates, the most common species of coagulase-negative staphylococci were Staphylococcus epidermidis (57%), Staphylococcus haemolyticus (24%), Staphylococcus hominis (8%), and others. The isolates showed high degree of resistance to benzyl penicillin (92%), oxacillin (85%), and cefoxitin (83%). No resistance to linezolid, tigecycline, and glycopeptides was detected. Conclusion: Staphylococcus epidermidis and Staphylococcus haemolyticus were the main coagulase-negative staphylococci isolates from several healthcare-associated infections such as bloodstream and urinary tract infection. Most of the isolates showed resistance responses to benzyl penicillin, oxacillin, and cefoxitin, while they were susceptible to glycopeptides, linezolid, and tigecycline, but intermediate response to glycopeptide was also observed.